The Effect of Spraying With Nano-Boron on Some Productive and Qualitative Traits of Six Genetic Combinations of Sugar Corn (Zea mays L. saccharata) in Salah al-Din Governorate - Marai, Manal Ali (American Journal of Botany and Bioengineering, 2025)
The experiment was conducted in Al-Mu’tasim sub-district, Samarra district, Salah al-Din Governorate, during the autumn season of 2023. Six genotypes of sweet corn (Gold Rush, Chocolate, 001, Seker Misir, Succar, Roi Soleal) were used, along with four levels of Nano boron spray (0, 6, 12, and 18 mg L-¹), applied according to a randomized complete block design (RCBD) with three replicates. The results showed that increasing the boron level significantly improved the total and biological yields, with the total yield increasing from 6165 kg ha⁻¹ when not sprayed to 8552 kg ha⁻¹ at 18 mg L⁻¹, and the biological yield from 13426 to 17064 kg ha⁻¹. The response of the genotypes also varied, with the 001 variety achieving the highest average total yield (7953 kg ha⁻¹) and biological (16120 kg ha⁻¹), while Seker Misir had the lowest. The interaction between varieties and boron levels showed that some varieties, such as 001 and Succar, respond best at the highest boron level. For qualitative traits, total sugars increased from 7.64% to 10.38%, and total soluble solids (TSS) from 7.12% to 8.68% with increasing boron, with the Chocolate variety recording the highest values (11.18% sugars and 11.18% TSS). Protein content also increased from 8.22% to 9.68%, with Succar responding best, while oil content decreased slightly from 4.18% to 4.00% at the highest boron level, with the highest oil content for the 001 variety (4.28%).